Assessing adipose tissue depot differences in thermogenesis during early life in sheep and browning response in humans with pheochromocytoma - Davies, Graeme R. (2017)
Obesity and associated comorbidities such as diabetes are currently major global health problems. It has been shown that individual sites or depots of fat have different properties and effects on whole body physiology. Of particular interest are depots that display thermogenic characteristics, known as brown or beige adipose tissue, which may be able to increase energy expenditure and clear excess glucose and lipids from the circulation. The aim of this thesis was to compare adipose tissue depots in terms of their capacity for thermogenesis in early life using sheep as an animal model and browning response to chronic adrenergic stress in humans with pheochromocytoma.